2010
DOI: 10.2478/s11536-010-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

A short overview of vitamin C and selected cells of the immune system

Abstract: AbstractVitamin C (ascorbic acid) is an essential water-soluble nutrient that primarily exerts its effect on a host defense mechanisms and immune homeostasis and is the most important physiological antioxidant. Stable intake of vitamin C is essential for life in humans because the body does not synthesize it. Even the numerous studies have demonstrated that vitamin C supplementation stimulates the immune system, prevents DNA damage and significantly decreases the risk of a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
(96 reference statements)
0
15
0
Order By: Relevance
“…It is well documented that immune cells are sensitive to oxidative stress because of the high content of polyunsaturated fatty acids in their plasma membranes and a high production of ROS, which is part of their normal function [ 22 ]. Intensive ROS production may induce apoptosis by oxidative stress or direct ROS damage to cellular components [ 23 , 24 , 25 ]. Cell death depends, in part, upon mitochondrial dysfunction, which if often characterized by increased production of ROS, increased membrane permeability and eventual release of cell death mediators from mitochondria [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that immune cells are sensitive to oxidative stress because of the high content of polyunsaturated fatty acids in their plasma membranes and a high production of ROS, which is part of their normal function [ 22 ]. Intensive ROS production may induce apoptosis by oxidative stress or direct ROS damage to cellular components [ 23 , 24 , 25 ]. Cell death depends, in part, upon mitochondrial dysfunction, which if often characterized by increased production of ROS, increased membrane permeability and eventual release of cell death mediators from mitochondria [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin C is a major component of the body anti-oxidant system and is known to provide protection from the toxic effects of many exogenous/endogenous toxicants, including reactive oxygen species (ROS). While ROS are generated as byproducts of normal aerobic respiration, they are also readily formed during inflammation and during host cell responses to exposure to environmental toxicants (McGregor and Biesalski 2006;Pavlovic and Sarac 2010). Because the data here showed that Vit C cotreatment appeared to block/mitigate toxicities in rabbits, we surmise that the splenotoxic effects of endosulfan may be mediated in great part by the formation of ROS and/or other agents that are subject to chemical reduction in situ.…”
Section: Discussionmentioning
confidence: 64%
“…Vitamin C depletion leads to inflammation or infection [37]. This is why blood levels of vitamin C drop during times of disease or infection.…”
Section: Resultsmentioning
confidence: 99%